PENGARUH PENERAPAN MODEL PBL TERINTEGRASI STEAM TERHADAP KEMAMPUAN BERPIKIR KREATIF DITINJAU DARI PEMAHAMAN KONSEP SISWA - Agus Budiyono; Hotimatul Husna; Arin Wildani (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2020)
THE EFFECT OF IMPLEMENTATION OF STEAM INTEGRATED PBL MODEL ON CREATIVE THINKING ABILITY JUDGED BY STUDENTS' UNDERSTANDING OF CONCEPTSAbstractThe ability to think creatively is a skill that can support students in 21st-century learning. This study aims to describe the effect of the application of the integrated PBL model and STEAM on the ability to think creatively in terms of students' conceptual understanding. The study used a pre-experimental method using one group pretest-posttest design, that is, only one experimental group without using a control group. The population was all class XI of SMAN 1 Pademawu with samples taken using cluster random sampling, namely only one class. Data were analyzed using two-way ANOVA. The result shows that there is a significant effect of the integrated PBL model and STEAM on high school students' creative thinking (Fhit = 177.189 α = 0.000 <α = 5%). Students 'high understanding of concepts has an impact on students' higher creative thinking abilities when compared to students who have low concept understanding (Fhit = 202,804 α = 0,000 <α = 5%). The interaction between the STEAM integrated PBL model and students 'understanding of the initial concept had a significant effect on students' creative thinking abilities, namely (Fhit = 5.406 α = 0,000 <α = 5%). AbstrakKemampuan berpikir kreatif menjadi kemampuan yang dapat menunjang siswa dalam pembelajaran abad 21. Penelitian ini bertujuan untuk mendeskripsikan pengaruh penerapan model PBL terintegrasi pendekatan STEAM terhadap kemampuan berpikir kreatif ditinjau dari pemahaman konsep siswa. Penelitian ini menggunakan metode pre-experiment dengan menggunakan desain one group pretest-posttest design yaitu hanya satu kelompok eksperimen dengan tanpa menggunakan kelompok kontrol. Populasinya adalah seluruh kelas XI SMAN 1 Pademawu dengan sampel diambil menggunakan cluster random sampling yakni hanya satu kelas saja. Data dianalisis menggunakan ANAVA Dua Jalur. Penelitian menunjukkan ada pengaruh yang siginifikan model PBL terintegrasi pendekatan STEAM terhadap berpikir kreatif siswa SMA (Fhit = 177.189 Pemahaman konsep siswa yang tinggi berdampak pada kemampuan berpikir kreatif siswa yang lebih tinggi pula jika dibandingkan dengan siswa yang memiliki pemahaman konsep rendah (Fhit = 202.804 . Interaksi antara model PBL terintegrasi STEAM dan pemahaman konsep awal siswa memberikan pengaruh yang signifikan terhadap kemampuan berpikir kreatif siswa yaitu sebesar (Fhit = 5.406 .